2018
DOI: 10.1134/s106235901804009x
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Microbiota under Diverse Conditions of Soil Moistening

Abstract: ⎯According to data on the abundance of taxonomic, physiological, and ecotrophic microbial groups, analysis of the seasonal changes in their composition under conditions of artificial (irrigation) and natural (wet land formation) soil moistening was carried out. It was revealed with statistical reliability that the greatest response to changes caused by different soil moistening modes was observed in the numbers of aerobic cellulose-degrading microorganisms, denitrifiers, and fungi. An increase in erosion resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…This increase could have been due to a number of factors that stimulated microbial activity including water addition, increase in temperature and provision of an organic amendment source. Studies have reported that soil irrigation can have significant effects on the soil microbial community and its functions (Lisetskii et al 2018). While soil moisture was not a variable in this study, soil wetting likely played a significant role in the initial shift in the soil microbiome and its metabolism of lignocellulose.…”
Section: Potential For Lignocellulose Degradation During Soil Biosolamentioning
confidence: 67%
See 1 more Smart Citation
“…This increase could have been due to a number of factors that stimulated microbial activity including water addition, increase in temperature and provision of an organic amendment source. Studies have reported that soil irrigation can have significant effects on the soil microbial community and its functions (Lisetskii et al 2018). While soil moisture was not a variable in this study, soil wetting likely played a significant role in the initial shift in the soil microbiome and its metabolism of lignocellulose.…”
Section: Potential For Lignocellulose Degradation During Soil Biosolamentioning
confidence: 67%
“…Studies have reported that soil irrigation can have significant effects on the soil microbial community and its functions (Lisetskii et al . ). While soil moisture was not a variable in this study, soil wetting likely played a significant role in the initial shift in the soil microbiome and its metabolism of lignocellulose.…”
Section: Discussionmentioning
confidence: 97%
“…Its representatives are well-known ‘universals’ with variable metabolic pathways [ 71 ] that can consume complex polymers [ 1 , 71 ]. They are resistant to low temperatures [ 5 ] and moisture fluctuations [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soil bacterial communities are connected by syntrophic, competitive and other synergistic and antagonistic interactions within themselves and with other components of the biota. Their taxonomic composition reflects the ecological balance resulting from the combined effects of biotic [7] and abiotic [8,9] factors, including controllable factors related to agricultural technology. The idea of controllability of processes occurring in the soil through the introduction of biofertilizers, stimulation or suppression of individual bacterial groups has far-reaching prospects.…”
Section: Introductionmentioning
confidence: 99%